Teaching cases in tourism, hospitality and events - Dixit, Saurabh Kumar; Piramanayagam, Senthilkumaran
"The tourism, hospitality and events industries comprise one of the largest and most diverse workforces in the world, creating high demand for graduates with strong technical and managerial competencies. Case-based learning encourages students to think, understand, and apply the concepts and theories they're taught into practical, everyday situations faced in the world of work. Providing a broad selection of extensive global cases, this book forms a comprehensive one-stop-shop resource for readers to test their analytical skill and abilities in solving complex management issues. Cases include teaching notes to reflect theoretical perspectives, as well as questions, detailed learning activities and solutions. The book covers: - General management, including innovation, ethics, and sustainability;- Strategic management, including business models, SWOT analyses and internationalisation;- Human resource management, including motivating employees, conflict management and work-life balance;- Marketing, including managing service quality, branding and new service development;- Financial management, including budgeting, risk management and forecasting;- Operations management, including food and beverage delivery, revenue management and health and safety. A useful and engaging read for students of tourism, hospitality and events, this book is also a valuable compilation of examples of practice for people working in industry."--